ANALYSIS OF FACTORS OF ENVIRONMENTAL HAZARD FOR THE WASTE STORAGE UNIT LLC "RUBIZHANSKYY KRASYTEL" - MIKHALKOVA, Nina; UDALOV, Igor (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Background. The article is devoted to environmental hazard factors, that can negatively affect the condition of the highly mineralized wastewater storage of LLC "Rubizhansky Krasytel". The relevance of the work is due to the existing environmental problems, that accompany the long-term operation of the man-made facility. Methods. The study employed an analysis of available information on the geological and hydrogeological conditions of the area and the technical state of the waste accumulation facility. Environmental risk assessment was carried out based on literary sources, cartographic materials, and logical analysis of the influence of natural and technogenic factors. Given the lack of access to the site, a conditional modeling approach was applied to simulate potential impact scenarios considering identified risk factors. Results. The main hazard factors, according to their origin, are divided into natural and man-made. It is established that the influence of natural hazard factors is due to the peculiarities of the territory where the man-made facility is located and global climate changes. The main processes that pose a potential threat to the spread of substances from the storage tank are described, both from the endogenous natural component (geological structure of the territory, hydrogeological conditions) and exogenous (climatic and hydrological conditions). It is noted that the location of the storage facility in the zone of influence of the North-Donetsk thrust contributes to the spread of substances from the storage facility in the geological environment. It is noted, that the condition of the structures partially reflects the manifestations of the influence of certain factors, but their further action can provoke an emergency situation on the storage tank. Сonclusions. The analyzed technogenic hazard factors indicate a number of adverse processes, the potential threat of which is directly related to the violation of the conditions of operation of the facility. At the same time, the presence of signs indicating damage to structures and communications is noted. The article determines that military hazard factors, which are technogenic, currently have the highest degree of probability of destructive impact on the storage facility. It is noted that the territory being under the control of third parties, namely the occupation forces, has created a rather dangerous situation, taking into account the material composition of the waste. Moreover, these circumstances nullify any ways to solve the existing environmental problems of the adjacent territory, making access to the facility impossible.